Experimental peri-implant mucositis around titanium and zirconia implants in comparison to a natural tooth: part 1—host-derived immunological parameters - Clever, Kim; Schlegel, Karl Andreas; Kniha, Heinz; Conrads, Georg; Rink, Lothar; Modabber, Ali; Hoelzle, Frank; Kniha, Kristian (International Journal of Oral and Maxillofacial Surgery, 2019)
The purpose of this study was to assess host-derived parameters around dental zirconia and titanium implants and natural teeth during the occurrence of mucositis. After 4 weeks of perfect oral hygiene, 16 clinically profiled patients were asked to refrain from oral hygiene for 2 weeks, resulting in experimental plaque accumulation. This was followed by 4 weeks of perfect oral hygiene to reverse the inflammation. Immunological samples were analyzed for interleukin 6 (IL-6), tumour necrosis factor alpha (TNF-α), and interleukin 1β (IL-1β). Immunological parameters were measured each week, starting at week 4 (session 2) and ending at week 10 (session 8). There were significant differences in IL-6 between the groups (zirconia vs. tooth and titanium vs. tooth), with unfavourable values for the tooth unit (P < 0.05). After reinstitution of oral hygiene, there was a significant increase in TNF-α values for the tooth but not for the zirconia and titanium implants. There were significant differences in IL-1β between the groups (zirconia vs. titanium and titanium vs. tooth), with higher IL-1β levels around titanium implants (P < 0.05). The soft tissue around titanium implants developed a stronger inflammatory response to experimental plaque accumulation in terms of IL-1β values, whereas the teeth presented an increase in IL-6 and TNF-α values.
CRIS-Team Scopus Importer:2019-08-13
Keywords: dental implant; experimental reversible mucositis; host response; plaque accumulation; titanium; zirconia

Experimental peri-implant mucositis around titanium and zirconia implants in comparison to a natural tooth: part 2-clinical and microbiological parameters - Clever, Kim; Schlegel, K. A.; Kniha, H.; Conrade, G.; Rink, Lothar; Modabber, A.; Hoelzle, F.; Kniha, Kristian (International Journal of Oral & Maxillofacial Implants, 2019)
The aim of this study was to assess the clinical and microbiological parameters around dental zirconia and titanium implants compared with natural teeth during experimental plaque accumulation. Clinical parameters were evaluated (gingival index, plaque index, bleeding on probing, and probing pocket depth). Microbiological samples were analyzed for total bacterial cell counts, as well as Tannerella forsythia and Prevotella intermedia counts. A statistically significant difference over time was observed in the groups in terms of the gingival index (P<0.001), plaque index (P<0.001), and bleeding on probing (P=0.039). The lowest mean total number of bacterial cells was measured around the teeth, followed by the zirconia implants; the highest values were found around the titanium implants. T. forsythia and P. intermedia values showed significant changes over time and sessions around the titanium implants. Compared to the soft tissues around zirconia implants and the teeth, those around titanium implants developed a stronger inflammatory response to experimental plaque accumulation in terms of the total number of bacterial cells and T. forsythia and P. intermedia values.
EVALuna2:206530